POST TRAUMATIC STRESS DISORDER PADA KORBAN PERDAGANGAN ORANG DI YAYASAN KUSUMA BONGAS, KABUPATEN INDRAMAYU - Ardina, Gameta Syifa; Pribowo, Pribowo (Indonesian Journal of Social Work, 2023)
The COVID-19 pandemic has increased the number of victims of trafficking in persons due to economic constraints. Victims of trafficking in persons experience various problems as a result of their traumatic experiences, making them vulnerable to experiencing indications of post-traumatic stress disorder (PTSD). Individuals with PTSD experience impairment in social functioning for more than six months. This research aims to determine the description of PTSD in trafficking victims, which can be seen from five aspects, namely re-experiencing, avoidance, negative alternations, hyperarousal, and social aspects. This research is descriptive research with quantitative methods. Respondents of this study were victims of trafficking in persons at the Kusuma Bongas Foundation in Indramayu using a census sample that used all members of the population as many as 32 people. The data collection instrument used was guided by the PTSD screening standard measurement tool published by DSM-V, namely PTSD Checklist-5 (PCL-5) with the addition of question items on social aspects. This instrument has been tested valid and reliable. The data collection technique used is the distribution of questionnaires with the home visit method. The results showed that there were 10 victims of trafficking who experienced indications of PTSD at the Kusuma Bongas Foundation with a percentage of 31.25% and all aspects of PTSD were included in the low category. The results of the problem analysis show that avoidance aspects and social aspects have high scores. The results showed that respondents tended to experience disturbances in their social aspects so that they needed a treatment program with reference to the perspective of social work